Kinetics and Mechanism of Flexible Nanoparticles-Catalyzed Piperidinolysis of Anionic Phenyl Salicylate: Flexible Nanoparticles: CTABr/M2X/H2O (M2X = 4-MeOSaNa2, 3-, 4-MeSaNa2) - Razak, Norazizah Abdul; Fagge, Ibrahim Isah; Elhefian, Esam Abdulkader; Khan, Mohammad Niyaz (Springer Verlag, 2019)
Apparent pseudo second-order rate constants, k X , for flexible nanoparticles, FNs, (CTABr/M 2 X/H 2 O)-catalyzed piperidinolysis of anionic phenyl salicylate, PSa − , at a constant [CTABr], 0.1 M piperidine (Pip) and temperature, were calculated from an empirical equation. CTABr = cetyltrimethylammonium bromide and X 2− = 4-methoxysalicylate (4-MeOSa 2− ) and 3-,4-methylsalicylate (3-,4-MeSa 2− ) with Sa 2− representing − O-C 6 H 3 CO 2 − . The values of k X /k 0 = μ measure the apparent rate enhancement due to FN catalysis for piperidinolysis of PSa − at a constant [CTABr] and temperature. The values of μ decrease with the increase in [CTABr] within the range of 5–15 mM. © 2019, Pleiades Publishing, Ltd.